Sleep habits, personal factors and environmental factors: a three-dimensional sleep model for Portuguese adolescents - Pinto, Joana Carneiro (2014)
Objectives: This study characterizes sleep’s adolescents considering habits, self-perceptions, and knowledge, explores the factors that underline their self-perceptions, and proposes a model to an integrative approach of sleep as framework of future researches and interventions. Methods: Participated 400 students (54.8% girls 45.3% boys), with a mean age of 15.33 years, attending the 9th and 11th grades, of two schools in Lisbon. They were assessed by the Questionnaire About Sleep for Adolescents (Rebelo-Pinto, 2010), which addresses 18 questions about sleep habits and routines, 5 about self-perceptions, and 20 about knowledge. Results: Quantitative results focused on: i) sleep duration, regularity and autonomy, verifying a marked irregularity in rise (4h04) and bedtime (2h18) hours, or total sleep time (2h06) comparing week and weekend; ii) on organization and functionality of the room and eating habits, whereas the main causes attributed to insufficient sleep are “noises in the room”, “watch TV until late”, and “being at the internet for hours”; and, iii) factors of cognitive and emotional nature such as knowledge and concerns, since the majority deemed to have “average” (45.5%) and “good” (23.0%) knowledge. From the qualitative exploration of self-perceptions, emerged in the environmental factors the daily activities in relation with sleep, and in the personal factors the knowledge and problems related to sleep. Conclusions: Results raised the possibility of developing a proposal for a three-dimensional model about sleep that addresses sleep habits, personal factors and environmental factors, and that can be used as a generator matrix of objectives for clinical and educational interventions.